Achieving Accurate and Efficient Load Flow Model in Distribution Networks Using Hybrid Linearization Approach - Wasiu O. Sulaimon; Ibrahim O. Habiballah; Muhammad Khalid; Fahad S. Al-Ismail (IEEE Access)
Load flow analysis is essential for the effective operation and planning of power systems. While non-linear methods provide high precision, their computational complexity poses challenges for real-time applications, making them less practical for dynamic environments. In contrast, linear methods, while computationally efficient, often sacrifice accuracy, which can lead to suboptimal decision-making in power system management. This paper introduces a novel hybrid linear approach that synergistically combines two established linear load flow methods to overcome these limitations. By integrating the strengths of both methods, the proposed technique significantly enhances the accuracy of load flow analysis without compromising computational efficiency. To validate the effectiveness of the hybrid approach, extensive testing was conducted across various distribution networks. The results demonstrate notable improvements in accuracy compared to traditional linear methods, making this hybrid approach a promising solution for load flow analysis in practical applications. This advancement not only contributes to the field of power systems but also paves the way for more reliable and efficient real-time operational strategies.